External lipid function in ethnic hairs. (13th March 2019) - Coderch, Luisa; Oliver, Marc A.; Carrer, Víctor; Manich, Albert M.; Martí, Meritxell
Abstract: Objective: The main aim of this study is to characterize the external lipids of different ethnic hairs and to study the contribution of the exogenous lipids on their physicochemical properties. Methods: On the extraction procedure, sebaceous lipids from the exterior of the fiber are removed. The influence of those free lipids on the hair properties, such as contact angle, mechanical characteristics, and sorption of water, will be evaluated to determine permeation characteristics of the keratin fibers. Relationship with lipid order was also determined by infrared spectroscopy (IR). Results: Lipid extraction indicates the greatest amount of total lipids for African hair. Caucasian lipid extracts present the higher melting point and phase transition temperatures. This could be related to higher hydration and lower diffusion coefficient of the Caucasian fibers. A decrease in moisture was found in the lipid‐extracted fibers. This diminution of the maximum water regain in all cases could be due to a higher water desorption. IR results indicate that Caucasian and moreover African native fibers present the most quantity of lipids, and the similar frequency of all fibers indicates a lamellar/orthorhombic order arrangement. Conclusion: The hexane/tert‐butanol extraction was demonstrated to modify not only cuticular but also cortex lipids. Exogenous lipid depletion in all fibers indicates a less water content and higher water desorption. However, lipid depleted Caucasian fibers presents an increase in the lipid order which could be related to the different saturation of the lipid extract and its improvement in breaking tenacity.